Mitochondria as a therapeutic target for cardiac ischemia-reperfusion injury (Review) - Marin, Wenwen (Int J Mol Med, 2021)
Acute myocardial infarction is the leading cause of cardiovascular-related mortality and chronic heart failure worldwide. As regards treatment, the reperfusion of ischemic tissue generates irreversible damage to the myocardium, which is termed 'cardiac ischemia-reperfusion (IR) injury'. Due to the large number of mitochondria in cardiomyocytes, an increasing number of studies have focused on the roles of mitochondria in IR injury. The primary causes of IR injury are reduced oxidative phosphorylation during hypoxia and the increased production of reactive oxygen species (ROS), together with the insufficient elimination of these oxidative species following reperfusion. IR injury includes the oxidation of DNA, incorrect modifications of proteins, the disruption of the mitochondrial membrane and respiratory chain, the loss of mitochondrial membrane potential (∆Ψm), Ca(2+) over-load, mitochondrial permeability transition pore formation, swelling of the mitochondria, and ultimately, cardiomyocyte necrosis. The present review article discusses the molecular mechanisms of IR injury, and summarizes the metabolic and dynamic changes occurring in the mitochondria in response to IR stress. The mitochondria are strongly recommended as a target for the development of therapeutic agents; however, the appropriate use of agents remains a challenge.